2021
DOI: 10.1002/cncr.33507
|View full text |Cite
|
Sign up to set email alerts
|

Observed‐to‐expected incidence ratios of second malignant neoplasms after radiation therapy for medulloblastoma: A Surveillance, Epidemiology, and End Results analysis

Abstract: BACKGROUND The authors analyzed the incidence and types of second malignant neoplasms (SMNs) in patients treated for medulloblastoma. METHODS The authors compared the incidence of SMNs after radiotherapy (RT) for medulloblastoma in patients treated in 1973‐2014 with the incidence in the general population with the multiple primary–standardized incidence ratio function of Surveillance, Epidemiology, and End Results 9. Observed‐to‐expected incidence (O/E) ratios and 95% confidence intervals (CIs) were reported f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…16 Others have suggested a higher SMN rate with the use of alkylating agents in addition to RT for medulloblastoma. 11,17 Finally, the OS rates were the same as those for patients with medulloblastoma in this study and were comparable to rates reported in the existing photon and proton literature, validating the efficacy of PT for this tumor. 11,14,17 Whether the incidence of SMN after RT can be reduced by using passively scattered protons requires further study and longer follow-up.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…16 Others have suggested a higher SMN rate with the use of alkylating agents in addition to RT for medulloblastoma. 11,17 Finally, the OS rates were the same as those for patients with medulloblastoma in this study and were comparable to rates reported in the existing photon and proton literature, validating the efficacy of PT for this tumor. 11,14,17 Whether the incidence of SMN after RT can be reduced by using passively scattered protons requires further study and longer follow-up.…”
Section: Discussionsupporting
confidence: 85%
“…11,17 Finally, the OS rates were the same as those for patients with medulloblastoma in this study and were comparable to rates reported in the existing photon and proton literature, validating the efficacy of PT for this tumor. 11,14,17 Whether the incidence of SMN after RT can be reduced by using passively scattered protons requires further study and longer follow-up. Chung et al performed a retrospective cohort study of 558 patients who received passive scatter PT at the Harvard Cyclotron matched by age, sex, year of treatment, histology, and site with 558 patients who received photons from the SEER data.…”
Section: Discussionsupporting
confidence: 85%
“…Finally, there is some controversy regarding radiation-induced tumors and the role of chemotherapy in contributing to their development. The combination of radiation and chemotherapy has been reported to have a synergistic effect on the development of treatment-induced gliomas 4 , 97 or result in a shorter latency period. 16 In contrast, others report statistically significant increases in the risk of glioma development with increasing radiation dose, but no further increased risk with the addition of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 6 A recent study of 1294 medulloblastoma patients treated with radiation therapy between 1973 and 2014 reported that these patients developed second central nervous system (CNS) tumors at 40 times the rate expected in the general population. 4 Furthermore, several large cohort studies have demonstrated a direct correlation between the cumulative dose of radiation received and the risk of subsequent CNS tumor development. 5 , 7 , 8 This is particularly pertinent for young children, as those under 5 years of age are more susceptible to the development of radiation-associated gliomas compared with children receiving radiotherapy at a later age.…”
mentioning
confidence: 99%
See 1 more Smart Citation